Negative active material, method of preparation, electrode sheet, battery, vehicle, and electric device
Patent Information
- Application Number
- CN202610433480.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请所要解决的技术问题是提供一种负极活性材料、制备方法、极片、电池、车辆和用电装置,以解决相关技术中硅材料的电荷传输性能不佳,限制了全固态电池的倍率性能的问题
本申请实施例所提供的负极活性材料,包括内核和离散设置于内核表面的包覆相,其中,内核包括硅基材料,包覆相包括卤化物电解质和导电碳材料中的至少一种;硅基材料具有较高的理论比容量,有利于提高电池的能量密度;卤化物电解质具有良好的离子传导性能,可以弥补硅基材料本征离子电导率低的缺陷,为活性离子的快速嵌入和脱出提供高效的传输通道,降低负极活性材料的离子传输阻力;导电碳材料具有良好的电子传导性能,能够在内核表面构建连续的电子传输网络,改善硅基材料的电子导电性,降低负极活性材料的电子传输阻力;进一步地,在包覆相包括卤化物电解质的情况下,离散设置的卤化物电解质可以在内核表面形成多个离子传输位点,提升活性离子的迁移速率,在包覆相包括导电碳材料的情况下,离散设置的导电碳材料可以在内核表面构建三维电子传导通路,降低负极活性材料的电子传输阻抗,从而可以从不同维度改善负极活性材料的电荷传输性能,进而提升基于本申请实施例提供的负极活性材料制备的电池的倍率性能。
Smart Images

Figure CN123017907A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a negative electrode active material, a preparation method, an electrode sheet, a battery, a vehicle, and an electrical device. Background Technology
[0002] All-solid-state batteries are energy storage devices that use solid electrolytes instead of traditional liquid electrolytes and separators, and have the characteristics of intrinsic safety, high energy density, long cycle life, and wide temperature range.
[0003] The negative electrode active material in all-solid-state batteries is generally pure silicon, such as micron-sized silicon or nano-sized silicon. However, silicon has poor charge transport performance, which limits the rate performance of all-solid-state batteries. Summary of the Invention
[0004] The technical problem to be solved by this application is to provide a negative electrode active material, a preparation method, an electrode sheet, a battery, a vehicle, and an electrical device to solve the problem that the poor charge transport performance of silicon materials in related technologies limits the rate performance of all-solid-state batteries.
[0005] To solve the above-mentioned technical problems, this application provides the following technical solution: This application proposes a negative electrode active material, which includes a core and a coating phase discretely disposed on the surface of the core, wherein the core includes a silicon-based material and the coating phase includes at least one of a halide electrolyte and a conductive carbon material.
[0006] Furthermore, the thickness of the coating phase is 1 nm to 30 nm and / or, The coating phase has a size of 10 nm to 100 nm in the direction parallel to the core surface; and / or, The coating phase has a coverage rate of 20% to 95% on the core surface.
[0007] Furthermore, the coating phase comprises a halide electrolyte, wherein the halide electrolyte satisfies at least one of the following: (1) The thickness of the halide electrolyte is 2nm~30nm; (2) The size of the halide electrolyte in the direction parallel to the core surface is 10 nm to 80 nm; (3) The coverage of the halide electrolyte on the core surface is 30%~80%; (4) The halide electrolyte includes at least one of Li3MX6 and LiMX4, wherein X includes any one of Cl, Br and I, and M includes any one of Y, In, Sc, Er and La.
[0008] Furthermore, the thickness of the halide electrolyte is 5 nm to 15 nm; and / or, the size of the halide electrolyte in the direction parallel to the core surface is 20 nm to 60 nm.
[0009] Furthermore, the coating phase comprises a conductive carbon material, wherein the conductive carbon material satisfies at least one of the following: (1) The thickness of the conductive carbon material is 1 nm to 10 nm; (2) The conductive carbon material has a size of 10 nm to 100 nm in the direction parallel to the core surface; (3) The conductive carbon material has a coverage rate of 20% to 70% on the surface of the core; (4) In the Raman spectrum of the conductive carbon material, the ratio of the intensity of the D peak to the intensity of the G peak is less than or equal to 1.1; (5) The in-plane reversible elongation of the conductive carbon material is greater than or equal to 10%; (6) The conductive carbon material includes atomically doped graphitized carbon.
[0010] Furthermore, the thickness of the conductive carbon material is 2nm~8nm.
[0011] Furthermore, the silicon-based material includes at least one of elemental silicon and silicon oxide.
[0012] Furthermore, the coating phase includes a halide electrolyte and a conductive carbon material; wherein the halide electrolyte is discretely disposed on a portion of the surface of the core, and the conductive carbon material is discretely disposed on a portion of the surface of the halide electrolyte and / or on a portion of the surface of the core not covered by the halide electrolyte.
[0013] Furthermore, the overlap area of the halide electrolyte and the conductive carbon material accounts for 10% to 40% of the core surface area; and / or, The halide electrolyte and the conductive carbon material have an overlapping region, in which the halide electrolyte and the conductive carbon material are chemically bonded.
[0014] Furthermore, the proportion of the exposed area on the surface of the core that is not covered by the coating phase is 5% to 80%.
[0015] Furthermore, the proportion of the exposed area on the surface of the core that is not covered by the coating phase is 5% to 40%.
[0016] Furthermore, the primary particle size in the core is 50nm~500nm; and / or, The core includes channels with a diameter of 2nm to 50nm.
[0017] Furthermore, the ionic conductivity of the negative electrode active material at 25°C is greater than or equal to 1×10⁻⁶. -4 S / cm; and / or, The negative electrode active material has an electronic conductivity greater than or equal to 1 S / cm at 25°C.
[0018] This application also proposes a method for preparing a negative electrode active material, used to prepare the negative electrode active material as described above, the preparation method comprising: Forming corresponding adhesion sites on the surface of silicon-based materials; Based on the attachment sites, a coating phase is prepared to obtain a negative electrode active material.
[0019] Further, forming corresponding adhesion sites on the surface of the silicon-based material includes: Silicon-based materials are heated in a mixed gas environment to obtain silicon-based materials with adhesion sites on their surface; The mixed gas includes hydrogen and an inert gas, and the proportion of hydrogen in the mixed gas is 1% to 15%.
[0020] Further, the preparation of the coating phase based on the attachment sites to obtain the negative electrode active material includes: A liquid dispersion system is prepared based on the first target silicon-based material, LiX and MX3, wherein X includes any one of Cl, Br and I, and M includes any one of Y, In, Sc, Er and La. The first target silicon-based material is a silicon-based material with conductive carbon material disposed on its surface or a silicon-based material with attachment sites formed on its surface. The liquid dispersion system is stirred to form discretely arranged halide electrolytes on the surface of the first target silicon-based material; The pH value of the liquid dispersion system is 6.5 to 8.5.
[0021] Further, the preparation of the coating phase based on the attachment sites to obtain the negative electrode active material includes: The second target silicon-based material is mixed with a carbon source to prepare a mixed raw material. The second target silicon-based material is a silicon-based material with a halide electrolyte on its surface or a silicon-based material with adhesion sites formed on its surface. The mixed raw materials are calcined to form discretely arranged conductive carbon materials on the surface of the second target silicon-based material; The preparation method satisfies at least one of the following: (1) The mass ratio of the second target silicon-based material to the carbon source is 1:0.25 to 1:0.4; (2) The gaseous environment in which the mixed raw materials are calcined includes hydrogen and inert gas, and the proportion of hydrogen in the mixed gas formed by hydrogen and inert gas is 1% to 15%; (3) The temperature for calcining the mixed raw materials is 400℃~1000℃; (4) The heating rate of the mixed raw material for calcination is greater than or equal to 30°C, and the calcination time of the mixed raw material is less than or equal to 15 min; (5) The calcination time for the mixed raw materials is 5 min to 15 min.
[0022] This application also proposes a negative electrode sheet, which includes the negative electrode active material as described above, or includes a negative electrode active material prepared by the method for preparing the negative electrode active material as described above.
[0023] This application also proposes a battery comprising a negative electrode as described above.
[0024] This application also proposes a vehicle that includes a battery as described above, the battery serving as a power source for the vehicle.
[0025] This application also proposes an electrical device comprising a battery as described above, the battery serving as a power source for the electrical device.
[0026] Compared with related technologies, the embodiments of this application have the following advantages: The negative electrode active material provided in this application includes a core and a coating phase discretely disposed on the surface of the core. The core includes a silicon-based material, and the coating phase includes at least one of a halide electrolyte and a conductive carbon material. The silicon-based material has a high theoretical specific capacity, which is beneficial for improving the energy density of the battery. The halide electrolyte has good ion conductivity, which can compensate for the low intrinsic ion conductivity of the silicon-based material, providing an efficient transport channel for the rapid insertion and extraction of active ions and reducing the ion transport resistance of the negative electrode active material. The conductive carbon material has good electronic conductivity, which can construct a continuous electron transport network on the surface of the core, improving the electronic conductivity of the silicon-based material and reducing the electron transport resistance of the negative electrode active material. Furthermore, when the coating phase includes a halide electrolyte, the discretely disposed halide electrolyte can form multiple ion transport sites on the surface of the core, increasing the migration rate of active ions. When the coating phase includes a conductive carbon material, the discretely disposed conductive carbon material can construct a three-dimensional electronic conduction pathway on the surface of the core, reducing the electron transport impedance of the negative electrode active material. This improves the charge transport performance of the negative electrode active material from different dimensions, thereby enhancing the rate performance of the battery prepared based on the negative electrode active material provided in this application.
[0027] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description
[0028] Figure 1 This is a schematic cross-sectional structure of a negative electrode active material provided in an embodiment of this application. Figure 1 ; Figure 2 This is a schematic cross-sectional structure of a negative electrode active material provided in an embodiment of this application. Figure 2 ; Figure 3 This is a schematic cross-sectional structure of a negative electrode active material provided in an embodiment of this application. Figure 3 ; Figure 4 This is a flowchart of the steps in a method for preparing a negative electrode active material provided in an embodiment of this application.
[0029] Explanation of reference numerals in the attached figures: 10-Core; 20-Coated phase; 21-Halide electrolyte; 22-Conductive carbon material. Detailed Implementation
[0030] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] In related technologies, the negative electrode active material in all-solid-state batteries is generally pure silicon, such as micron-sized or nano-sized silicon. Silicon has a theoretical specific capacity of up to 4200 mAh / g, which is more than 10 times that of commercial graphite negative electrodes (372 mAh / g), significantly improving the overall energy density of the battery and meeting the requirements of long-range electric vehicles and high-rate energy storage devices. However, silicon has poor charge transport performance, specifically manifested in its low intrinsic ionic conductivity. The insertion and extraction paths of active ions (e.g., lithium ions) within silicon are long, and the diffusion resistance is high. This results in lag in the transport of active ions in the negative electrode active material and rapid capacity decay during high-rate charge and discharge. In addition, silicon has poor electronic conductivity, leading to slow electron migration within the negative electrode active material and significant polarization effects, further limiting the rate performance of all-solid-state batteries.
[0032] Furthermore, the volume change rate of silicon materials during the insertion and extraction of active ions is as high as 300%. This not only leads to severe particle pulverization of the negative electrode active material during charge-discharge cycles, but also causes interfacial delamination between the negative electrode active material and the solid electrolyte in the all-solid-state battery. This results in frequent interruptions of electron and ion transport channels, exacerbating the instability of ion and electron transport in the negative electrode active material. Consequently, the internal resistance of the negative electrode sheet prepared based on the negative electrode active material increases sharply, leading to a deterioration in the rate performance and a reduction in the lifespan of the all-solid-state battery.
[0033] To address the aforementioned technical problems, this application provides a negative electrode active material, as described above. Figures 1 to 3 The negative electrode active material includes a core 10 and a coating phase 20 discretely disposed on the surface of the core 10, wherein the core 10 includes a silicon-based material and the coating phase 20 includes at least one of a halide electrolyte 21 and a conductive carbon material 22.
[0034] In some embodiments, the morphology of the coating phase 20 discretely disposed on the surface of the core 10 may include, but is not limited to, island-like, granular, discontinuous thin film, etc.
[0035] In some embodiments, refer to Figure 1 The coating phase 20 includes a halide electrolyte 21, which is discretely disposed on a portion of the surface of the core 10. This facilitates the formation of multiple dispersed ion transport sites on the surface of the core 10. Utilizing the excellent ion conductivity of the halide electrolyte 21, the inherent low ion conductivity of silicon-based materials is compensated for. It provides an omnidirectional contact transport channel on the surface of the core 10 for the rapid insertion and extraction of active ions. At the same time, the discrete placement of the halide electrolyte 21 on a portion of the surface of the core 10 can also prevent the agglomeration of the halide electrolyte 21 from blocking the ion transport channels, thereby reducing the ion transport resistance of the negative electrode active material, increasing the migration rate of active ions in the negative electrode active material, and improving the ion conductivity of the negative electrode active material. This, in turn, helps to slow down the capacity decay rate of the battery and improve the rate performance and cycle stability of the battery.
[0036] In some embodiments, refer to Figure 2The coating phase 20 includes a conductive carbon material 22, which is discretely disposed on a portion of the surface of the core 10. Based on its excellent electronic conductivity, the discretely disposed conductive carbon material 22 can construct a three-dimensional electronic conduction pathway on the surface of the core 10. Without covering the entire surface of the core 10, a continuous electron transport network is formed on the surface of the core 10. This not only improves the electronic conductivity of the silicon-based material, reduces the electronic transport impedance of the negative electrode active material, and increases the electronic conductivity of the negative electrode active material, but also avoids the problem of blocked ion transport paths caused by the complete coating of the surface of the core 10. This is beneficial to improving the capacity retention rate of the battery under high-rate charge and discharge conditions and optimizing the rate performance of the battery.
[0037] In some embodiments, refer to Figure 3 The coating phase 20 includes a halide electrolyte 21 and a conductive carbon material 22. While using the halide electrolyte 21 to improve the ionic conductivity of the negative electrode active material, the conductive carbon material 22 is used to improve the electronic conductivity of the negative electrode active material, which is beneficial to further improve the rate performance and cycle stability of the battery.
[0038] In some embodiments, the halide electrolyte 21 is discretely disposed on a portion of the surface of the core 10, and the conductive carbon material 22 is discretely disposed on the portion of the surface of the core 10 not covered by the halide electrolyte 21. This allows the halide electrolyte 21 and the conductive carbon material 22 to construct an ion-electron dual-pathway synergistic transport system on the surface of the core 10 through a discretely distributed synergistic arrangement. By utilizing the good ion conduction performance of the halide electrolyte 21 to compensate for the low intrinsic ion conductivity of silicon-based materials and improve the ion conductivity of the negative electrode active material, the continuous electron transport network formed by the discretely disposed conductive carbon material 22 on the surface of the core 10 also improves the electronic conductivity of the negative electrode active material. In some embodiments, conductive carbon material 22 is discretely disposed on a portion of the surface of the core 10, and halide electrolyte 21 is discretely disposed on a portion of the surface of conductive carbon material 22 and / or on a portion of the surface of the core 10 not covered by conductive carbon material 22. The discretely disposed conductive carbon material 22 forms a continuous electron transport network on the surface of the core 10, which can directly improve the electronic conductivity of silicon-based materials, increase the electronic conductivity of negative electrode active materials, and lay the foundation for rapid charge migration in negative electrode active materials. Furthermore, the discretely disposed halide electrolyte 21 on the surface of conductive carbon material 22 can further form ion transport sites on the electron transport network formed by conductive carbon material 22, realizing close-range synergistic transport of ions and electrons and reducing interfacial resistance during charge transport. The discretely disposed halide electrolyte 21 on the portion of the surface of the core 10 not covered by conductive carbon material 22 can supplement ion transport channels on the surface of the core 10 not covered by conductive carbon material 22, effectively improving the ion conductivity of silicon-based materials. Thus, through the spatial complementarity of ion transport channels and electron transport channels, the charge transport efficiency of negative electrode active materials is improved, thereby improving the rate performance of the battery and extending the cycle life of the battery.
[0039] Furthermore, in this embodiment, the discrete arrangement of the coating phase 20 on the surface of the core 10 can reduce the constraint of the coating phase 20 on the volume change of the core 10, reserving buffer space for the volume change of the core 10 during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles, which not only helps improve the cycle structure stability of the negative electrode active material, but also improves the interface quality between the negative electrode active material and the electrolyte in the battery, improves the stability of ion and electron transport of the negative electrode active material, and reduces the internal resistance of the negative electrode sheet prepared based on the negative electrode active material, which is beneficial to further improve the rate performance and cycle life of the battery. In addition, the conductive carbon material 22 can generate corrugated expansion and contraction with the volume change of the core 10, providing a dual electrical and mechanical buffer for the negative electrode active material during charge-discharge cycles.
[0040] It should be noted that, Figures 1 to 3The shapes of the core 10, the coating phase 20, and the stacking of the halide electrolyte 21 and conductive carbon material 22 in the coating phase 20 shown are merely examples and do not constitute a limitation on the shapes of the core 10, the coating phase 20, and the stacking of the halide electrolyte 21 and conductive carbon material 22 in the coating phase 20 in this embodiment. In actual application scenarios, the shapes of the core 10, the specific shapes of the coating phase 20, and the stacking of the halide electrolyte 21 and conductive carbon material 22 in the coating phase 20 can be set as needed.
[0041] In the negative electrode active material provided in this application embodiment, the coating phase is discretely disposed on the core surface; the core includes a silicon-based material, which has a high theoretical specific capacity, which is beneficial to improving the energy density of the battery; the coating phase includes at least one of a halide electrolyte and a conductive carbon material. The halide electrolyte has good ion conductivity, which can compensate for the low intrinsic ion conductivity of the silicon-based material, providing an efficient transport channel for the rapid insertion and extraction of active ions, reducing the ion transport resistance of the negative electrode active material, and improving the ion conductivity of the negative electrode active material. The conductive carbon material has good electronic conductivity, which can construct a continuous electron transport network on the core surface, improve the electronic conductivity of the silicon-based material, reduce the electron transport resistance of the negative electrode active material, and improve the electronic conductivity of the negative electrode active material. Furthermore, the discretely disposed halide electrolyte can form multiple ion transport sites on the core surface, improving the migration rate of active ions, and the discretely disposed conductive carbon material can construct a three-dimensional electron conduction pathway on the core surface, reducing the electron transport impedance of the negative electrode active material. Thus, this application embodiment can improve the charge transport performance of the negative electrode active material from different dimensions, and improve the rate performance of the battery prepared based on the negative electrode active material provided in this application embodiment.
[0042] In some embodiments, the thickness of the coating phase is 1 nm to 30 nm. Within this range, while ensuring that the coating phase fully plays its role in improving the charge transport performance of the negative electrode active material and enhancing the rate performance of the battery, it can also increase the energy density of the battery. Specifically, the thickness of the coating phase can be one of 1 nm, 5 nm, 15 nm, 20 nm, and 30 nm, or any value between two of them.
[0043] The thickness of the coating phase refers to the size of the coating phase in the radial direction of the core.
[0044] In some embodiments, the size of the coating phase in the direction parallel to the core surface is 10 nm to 100 nm. This avoids the coating phase completely covering the core surface, improving battery energy density while also providing a buffer space for volume changes in the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles, enhancing the cycle stability of the negative electrode active material and improving the interface quality between the negative electrode active material and the electrolyte in the battery. Furthermore, it promotes the formation of effective ion transport sites and / or three-dimensional electron conduction pathways on the core surface, thereby improving the charge transport performance of the negative electrode active material. Specifically, the size of the coating phase in the direction parallel to the core surface can be one of 10 nm, 30 nm, 60 nm, 90 nm, and 100 nm, or any value between two of these.
[0045] It is understood that the size of the coating phase in the direction parallel to the core surface refers to the spread size of a single discrete coating phase on the core surface; in some embodiments, the size of the coating phase in the direction parallel to the core surface is the maximum value of the spread size of a single discrete coating phase on the core surface.
[0046] In some embodiments, the coverage of the coating phase on the core surface is 20% to 95%. Within this range, on the one hand, it avoids the coating phase completely covering the core surface, thereby increasing the battery energy density while reserving buffer space for volume changes in the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles and improves the interface quality between the negative electrode active material and the electrolyte in the battery. On the other hand, it promotes the formation of effective ion transport sites and / or three-dimensional electron conduction pathways on the core surface by the coating phase, thereby improving the charge transport performance of the negative electrode active material. Specifically, the coverage of the coating phase on the core surface can be one of 20%, 40%, 50%, 70%, 80%, and 95%, or any value between two of these.
[0047] The coverage rate of the coating phase on the kernel surface refers to the percentage of the area covered by the coating phase relative to the kernel surface area.
[0048] In some embodiments, the coating phase includes a halide electrolyte.
[0049] In some embodiments, the thickness of the halide electrolyte is 2 nm to 30 nm. Within this range, while ensuring that the halide electrolyte fully compensates for the low intrinsic ionic conductivity of silicon-based materials and improves the ionic conductivity of the negative electrode active material, it can also increase the energy density of the battery. Specifically, the thickness of the halide electrolyte can be one of 2 nm, 10 nm, 15 nm, 20 nm, 25 nm, and 30 nm, or any value between two of them. The thickness of the halide electrolyte refers to its radial dimension in the core direction.
[0050] In some embodiments, the size of the halide electrolyte in the direction parallel to the core surface is 10 nm to 80 nm. Within this range, on the one hand, it can prevent the halide electrolyte from completely covering the core surface, thereby increasing the battery energy density and reserving buffer space for volume changes in the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles and improves the interface quality between the negative electrode active material and the electrolyte in the battery. On the other hand, it can promote the formation of effective ion transport sites on the core surface by the halide electrolyte, thereby increasing the migration rate of active ions in the negative electrode active material and improving the ionic conductivity of the negative electrode active material. Specifically, the size of the halide electrolyte in the direction parallel to the core surface can be one of 10 nm, 25 nm, 50 nm, 65 nm, 70 nm, and 80 nm, or any value between two of them. Here, the size of the halide electrolyte in the direction parallel to the core surface refers to the spread size of a single discrete halide electrolyte on the core surface; in some embodiments, the size of the halide electrolyte in the direction parallel to the core surface is the maximum value of the spread size of a single discrete halide electrolyte on the core surface.
[0051] In some embodiments, the halide electrolyte coverage on the core surface is 30% to 80%. Within this range, on the one hand, it avoids the halide electrolyte completely covering the core surface, thus improving battery energy density while reserving buffer space for volume changes in the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles and improves the interface quality between the negative electrode active material and the electrolyte in the battery. On the other hand, it promotes the formation of effective ion transport sites on the core surface by the halide electrolyte, thereby increasing the migration rate of active ions in the negative electrode active material and improving the ionic conductivity of the negative electrode active material. Specifically, the halide electrolyte coverage on the core surface can be one of 30%, 40%, 50%, 60%, 70%, and 80%, or any value between two of these. The halide electrolyte coverage on the core surface refers to the percentage of the halide electrolyte coverage area relative to the core surface area.
[0052] In some embodiments, the halide electrolyte includes at least one of Li3MX6 and LiMX4, wherein X includes any one of Cl, Br and I, and M includes any one of Y, In, Sc, Er and La. This is beneficial for further improving the ionic conductivity of the halide electrolyte at room temperature, building an efficient transport channel for the rapid insertion and extraction of active ions, specifically improving the ionic conductivity of silicon-based materials, reducing the ion transport impedance of the negative electrode active material, and improving the ionic conductivity of the negative electrode active material, thereby improving the rate performance of the battery. At the same time, by utilizing the coordination characteristics of cation metals, the surface chemical potential of the halide electrolyte can be controlled, enabling it to form a stable interfacial contact with the core and conductive carbon materials, suppressing interfacial side reactions and the generation of high-resistance products, and improving the cycle stability of the negative electrode active material.
[0053] In some embodiments, the thickness of the halide electrolyte is 5 nm to 15 nm. Within this range, the role of the halide electrolyte in compensating for the low intrinsic ionic conductivity of silicon-based materials and improving the ionic conductivity of the negative electrode active material can be fully utilized, while further shortening the ion migration distance and optimizing the proportion of the halide electrolyte in the negative electrode active material, thereby increasing the energy density of the battery. Specifically, the thickness of the halide electrolyte can be one of 5 nm, 8 nm, 10 nm, 13 nm, and 15 nm, or any value between two of them.
[0054] In some embodiments, the size of the halide electrolyte in the direction parallel to the core surface is 20 nm to 60 nm. Within this range, the continuity and effectiveness of ion transport sites can be further optimized while avoiding the electrolyte from completely covering the core surface and reserving volume buffer space for the core. At the same time, by precisely controlling the size of the halide electrolyte in the direction parallel to the core surface, the synergistic improvement of the ionic conductivity, cycle stability and energy density of the negative electrode active material can be achieved.
[0055] In some embodiments, the coating phase comprises a conductive carbon material.
[0056] In some embodiments, the thickness of the conductive carbon material is 1 nm to 10 nm. Within this range, while ensuring that the conductive carbon material fully plays its role in improving the electronic conductivity of silicon-based materials and increasing the electronic conductivity of the negative electrode active material, it can also improve the energy density of the battery. Specifically, the thickness of the conductive carbon material can be one of 1 nm, 3 nm, 5 nm, 8 nm, and 10 nm, or any value between two of them. The thickness of the conductive carbon material refers to its radial dimension in the core direction.
[0057] In some embodiments, the size of the conductive carbon material in the direction parallel to the core surface is 10 nm to 100 nm. Within this range, on the one hand, it can prevent the conductive carbon material from completely covering the core surface, thereby improving the battery energy density and reserving buffer space for volume changes of the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles and improves the interface quality between the negative electrode active material and the electrolyte in the battery. On the other hand, it can promote the formation of a continuous electron transport network of the conductive carbon material on the core surface, thereby improving the electronic conductivity of the silicon-based material and reducing the electron transport impedance of the negative electrode active material. Specifically, the size of the conductive carbon material in the direction parallel to the core surface can be one of 10 nm, 30 nm, 60 nm, 90 nm, and 100 nm, or any value between two of them. Here, the size of the conductive carbon material in the direction parallel to the core surface refers to the spreading size of a single discrete conductive carbon material on the core surface; in some embodiments, the size of the conductive carbon material in the direction parallel to the core surface is the maximum value of the spreading size of a single discrete conductive carbon material on the core surface.
[0058] In some embodiments, the coverage rate of the conductive carbon material on the core surface is 20% to 70%. Within this range, on the one hand, it avoids the conductive carbon material completely covering the core surface, thereby increasing the battery energy density and reserving buffer space for volume changes in the core during charge-discharge cycles. This reduces the probability of particle breakage and pulverization of the negative electrode active material during charge-discharge cycles and improves the interface quality between the negative electrode active material and the electrolyte in the battery. On the other hand, it promotes the formation of a continuous electron transport network on the core surface by the conductive carbon material, thereby improving the electronic conductivity of the silicon-based material and reducing the electron transport impedance of the negative electrode active material. Specifically, the coverage rate of the conductive carbon material on the core surface can be one of 20%, 30%, 50%, 60%, and 70%, or any value between two of these. The coverage rate of the conductive carbon material on the core surface refers to the percentage of the core surface area covered by the conductive carbon material.
[0059] In some embodiments, in the Raman spectrum of the conductive carbon material, the ratio of the intensity of the D peak to the intensity of the G peak is less than or equal to 1.1. The G peak represents the Raman spectrum of the conductive carbon material at 1580 cm⁻¹. -1 The nearby characteristic peaks are characteristic peaks of graphitic ordered carbon structures. The intensity of the G peak is related to the sp in conductive carbon materials. 2 The content of hybrid carbon is positively correlated with the lattice order; the D peak represents the Raman spectrum of conductive carbon materials at 1350 cm⁻¹. -1 The characteristic peaks in the vicinity are characteristic peaks of the disorder of conductive carbon materials. The intensity of the D peak is positively correlated with the defect density and disordered carbon content of conductive carbon materials.
[0060] In this embodiment, by controlling the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum of the conductive carbon material to be less than or equal to 1.1, the conductive carbon material can possess both a moderate degree of graphitization and a moderate defect structure. The ordered graphite lattice structure in the conductive carbon material can form a continuous electron transport network on the core surface, improving the electron migration rate and enhancing the electronic conductivity of the silicon-based material. Meanwhile, the moderate defect structure can form a porous structure in the conductive carbon material and improve its flexibility. The porous structure and flexibility of the conductive carbon material can provide further buffer space for changes in the volume of the core, reducing the probability of particle breakage and pulverization of the negative electrode active material particles due to drastic volume changes, and further improving the cycle stability of the negative electrode active material.
[0061] In some embodiments, the in-plane reversible elongation of the conductive carbon material is greater than or equal to 10%. Within this range, the conductive carbon material can absorb the volume expansion and contraction of the core during charge-discharge cycles through its own in-plane reversible elongation, providing a flexible buffer space for the volume change of the core. This effectively alleviates the stress impact caused by the volume change of the core on the coating phase during charge-discharge cycles, reducing the probability of the negative electrode active material particles breaking or pulverizing. At the same time, during the in-plane reversible stretching and deformation, the conductive carbon material can still maintain close contact with the core surface and the halide electrolyte surface, improving the reliability of the electron transport network formed on the core surface. This not only improves the rate performance of the battery but also enhances the cycle structure stability of the negative electrode active material, extending the cycle life of the battery.
[0062] In some embodiments, the conductive carbon material includes atomically doped graphitized carbon, which facilitates the modulation of the band structure of graphitized carbon through heteroatom doping modification, introduces additional carrier transport sites, reduces electron transport impedance, and improves the conductivity of the conductive carbon material. This, in turn, improves the electronic conductivity of silicon-based materials, reduces the electron transport impedance of the negative electrode active material, and increases the electron transport rate in the negative electrode active material. In some embodiments, atomically doped graphitized carbon may include at least one of N-doped graphitized carbon, P-doped graphitized carbon, S-doped graphitized carbon, and multi-heteroatom co-doped graphitized carbon.
[0063] In some embodiments, the thickness of the conductive carbon material is 2 nm to 8 nm. Within this range, the role of the conductive carbon material in improving the electronic conductivity of silicon-based materials and increasing the electronic conductivity of the negative electrode active material can be fully utilized, while further shortening the electron conduction distance and optimizing the proportion of the conductive carbon material in the negative electrode active material, thereby increasing the energy density of the battery. Specifically, the thickness of the conductive carbon material can be one of 2 nm, 3 nm, 5 nm, 7 nm, and 8 nm, or any value between two of them.
[0064] In some embodiments, the silicon-based material includes at least one of elemental silicon (Si) and silicon oxide (SiO x , 0<x<2), wherein the ultra-high theoretical specific capacity of elemental silicon can greatly increase the energy density of the negative electrode active material. In the crystal structure of silicon oxide, the presence of Si-O bonds can limit the migration and agglomeration of silicon atoms, which is beneficial to reducing the volume change rate of the core during charge and discharge cycles, thereby reducing the probability of particle cracking and pulverization of the negative electrode active material, and improving the cyclic structural stability of the negative electrode active material. In the scenario where the silicon-based material includes both elemental silicon and silicon oxide, both the energy density and cyclic structural stability of the negative electrode active material can be achieved.
[0065] In the related art, a single and continuous coating phase is also provided on the surface of the silicon material to improve the charge transport performance of the silicon material, which not only cannot simultaneously increase the ionic conductivity and electronic conductivity of the silicon material, but also the continuous coating phase completely covers the surface of the silicon material, resulting in the coating phase being prone to cracking, peeling and other problems due to stress concentration during the charge and discharge cycles, causing a sharp increase in interfacial impedance, and ultimately resulting in the dual attenuation of the rate performance and cycle stability of the battery.
[0066] In order to solve the above problems, in the embodiments of the present application, in some embodiments, the coating phase includes a halide electrolyte and a conductive carbon material; wherein the halide electrolyte is discretely disposed on part of the surface of the core, and the conductive carbon material is discretely disposed on part of the surface of the halide electrolyte and / or part of the surface of the core not covered by the halide electrolyte. In some embodiments, the halide electrolyte is discretely disposed on part of the surface of the core, and the conductive carbon material is discretely disposed on part of the surface of the halide electrolyte; in some embodiments, the halide electrolyte is discretely disposed on part of the surface of the core, and the conductive carbon material is discretely disposed on part of the surface of the core not covered by the halide electrolyte; in some embodiments, the halide electrolyte is discretely disposed on part of the surface of the core, and the conductive carbon material is discretely disposed on part of the surface of the halide electrolyte as well as part of the surface of the core not covered by the halide electrolyte.
[0067] In this embodiment, the coating phase includes a halide electrolyte and a conductive carbon material. The halide electrolyte is discretely disposed on a portion of the core surface, and the conductive carbon material is discretely disposed on a portion of the halide electrolyte surface and / or the portion of the core surface not covered by the halide electrolyte. The discretely disposed halide electrolyte can form independent and efficient ion transport sites on the core surface, compensating for the low intrinsic ion conductivity of silicon-based materials and improving the ion conductivity of the negative electrode active material. The discretely disposed conductive carbon material can form a continuous electron transport network in the exposed areas on the surface of the halide electrolyte and / or the core surface, improving the electronic conductivity of the negative electrode active material. At the same time, the discretely disposed conductive carbon material does not block the migration path of ions, realizing parallel transport of ions and electrons through dual pathways, which is beneficial to significantly improve the charge transport efficiency of the negative electrode active material and the rate performance of the battery.
[0068] In some embodiments, the overlap area of the halide electrolyte and the conductive carbon material accounts for 10% to 40% of the core surface area. Within this range, a coupling interface between the halide electrolyte and the conductive carbon material can be formed on the core surface, constructing an efficient ion-electron coupling transport channel. This achieves a synergistic improvement in the ionic conductivity and electronic conductivity of the negative electrode active material, improving the charge transport performance of the negative electrode active material from different dimensions, and thereby enhancing the rate performance of the battery prepared based on the negative electrode active material provided in the embodiments of this application. Specifically, the overlap area of the halide electrolyte and the conductive carbon material in the core surface area can be one of 10%, 20%, 25%, 30%, and 40%, or any value between two of these.
[0069] In some embodiments, the halide electrolyte and the conductive carbon material have an overlapping region. In the overlapping region, the halide electrolyte and the conductive carbon material are chemically bonded, thereby forming a chemical bonding interface between the halide electrolyte and the conductive carbon material. This is beneficial to improving the interface stability between the halide electrolyte and the conductive carbon material, enhancing the ability of the coating phase to resist core volume changes, and reducing the charge transport barrier between the interface of the halide electrolyte and the conductive carbon material, thereby achieving synergistic optimization of the cycle stability and rate performance of the negative electrode active material.
[0070] In some embodiments, nitrogen-containing groups on the surface of the nitrogen-containing conductive carbon material react with the metal active sites of the halide electrolyte to form CNM covalent bonds; in some embodiments, Si-H groups on the surface of the silicon-based core react synergistically with CN groups on the surface of the conductive carbon material to form a Si-HC bond structure; in some embodiments, carbon free radicals on the surface of the conductive carbon material recombine with the metal-halogen bonds of the halide electrolyte to form covalent bonds; in some embodiments, a silane coupling agent bridges the conductive carbon material and the halide electrolyte to form a bridging bond structure of conductive carbon material-silane coupling agent-halide electrolyte.
[0071] In some embodiments, the proportion of the exposed area not covered by the coating phase on the surface of the core is 5% to 80%. Within this range, the ionic and electronic conductivity of the negative electrode active material can be improved, while buffer space is reserved for volume changes of the core during charge-discharge cycles. This further improves the cycle structure stability of the negative electrode active material, enhances the interface quality between the negative electrode active material and the electrolyte in the battery, and improves the stability of ion and electron transport in the negative electrode active material. Specifically, the proportion of the exposed area not covered by the coating phase on the surface of the core can be one of 5%, 20%, 50%, 60%, 70%, and 80%, or any value between two of these.
[0072] In some embodiments, the percentage of exposed areas on the surface of the core that are not covered by the coating phase refers to the percentage of the area of the exposed area relative to the surface area of the core. In some embodiments, the sum of the percentage of exposed areas on the surface of the core that are not covered by the coating phase and the percentage of the coating phase coverage on the core surface is 100%.
[0073] In some embodiments, the proportion of the exposed area not covered by the coating phase on the surface of the core is 5% to 40%. Within this range, while improving the ionic and electronic conductivity of the negative electrode active material, sufficient buffer space is reserved for the volume change of the core during charge-discharge cycles. This is beneficial for improving the cycle structure stability of the negative electrode active material and improving the interface quality between the negative electrode active material and the electrolyte in the battery. Specifically, the proportion of the exposed area not covered by the coating phase on the surface of the core can be one of 5%, 10%, 15%, 30%, 35%, and 40%, or any value between two of them.
[0074] In some embodiments, the total open pore volume of the core surface not covered by the coating phase is greater than or equal to 30%, which can promote the insertion or extraction of active ions within a 10s timescale, and can significantly improve the ion migration rate of the negative electrode active material and the rate performance of the battery.
[0075] Therefore, in the embodiments of this application, the "dual-spot" heterogeneous coating phase formed by the halide electrolyte and conductive carbon material discretely disposed on the core surface ensures both high ionic conductivity and high electronic conductivity of the negative electrode active material. Through the local overlap of the halide electrolyte and conductive carbon material, as well as the exposed window on the core surface, adaptive adjustment of core volume changes can be achieved. This improves the rate performance of the battery, enhances the cycle structure stability of the negative electrode active material, and extends the cycle life of the battery.
[0076] In some embodiments, the primary particle size in the core is 50 nm to 500 nm. The particle size of the primary particle in the core refers to the particle size of a single silicon-based material particle in the silicon-based material constituting the core. In this embodiment, the particle size of the primary particle in the core is controlled within the range of 50 nm to 500 nm, which can shorten the diffusion path of active ions inside the core and improve the active ion transport efficiency. At the same time, the nanoscale particle size of the primary particle in the core can alleviate the volume change rate of the silicon-based material during charge-discharge cycles, reduce the problems of core cracking and pulverization, improve the structural integrity of the core and the structural integrity of the coating phase discretely set on the core surface, which is beneficial to improving the cycle capacity retention rate and electrochemical performance stability of the negative electrode active material.
[0077] In some embodiments, the core includes channels with a diameter of 2 nm to 50 nm. These channels can be confined channels, which facilitates the absorption of volume changes generated during charge-discharge cycles, reduces the probability of fragmentation and pulverization of the negative electrode active material particles, further improves the cycle stability of the negative electrode active material, and helps extend the battery's cycle life.
[0078] In some embodiments, the core includes channels and the coating phase includes conductive carbon material. The channels in the core and the fish-scale-like folds on the surface of the conductive carbon material can synergistically absorb the volume change generated by the core during charge-discharge cycles, thereby further improving the cycle stability of the negative electrode active material. In some embodiments, through the synergistic effect of the channels in the core and the fish-scale-like folds on the surface of the conductive carbon material, more than 300% of the volume change rate generated by the core can be absorbed, reducing the radial strain of the negative electrode active material to less than 5%.
[0079] The channels in the core include through channels and / or semi-through channels. In some embodiments, electrochemical etching, template method, sol-gel method and other processes can be used to form channels with a diameter of 2nm to 50nm inside the core.
[0080] In some embodiments, the ionic conductivity of the negative electrode active material at 25°C is greater than or equal to 1×10⁻⁶. - 4 Within the range of S / cm, the transport resistance of active ions inside the negative electrode active material can be reduced, the ion migration rate can be accelerated, and thus the rate performance and cycle life of the battery can be improved.
[0081] In some embodiments, the electronic conductivity of the negative electrode active material at 25°C is greater than or equal to 1 S / cm. Within this range, the electron transport impedance inside the negative electrode active material can be effectively reduced, the ohmic loss during charge-discharge cycles can be reduced, and the rate performance, charge-discharge efficiency and cycle stability of the battery can be improved.
[0082] Reference Figure 4 This application also provides a flowchart of a method for preparing a negative electrode active material, the method comprising: Step S101: Form corresponding adhesion sites on the surface of the silicon-based material.
[0083] Step S102: Prepare a coating phase based on the attachment sites to obtain a negative electrode active material.
[0084] The method for preparing the negative electrode active material provided in this application embodiment can realize the preparation of the negative electrode active material as described in any of the preceding claims. The negative electrode active material includes a core formed of silicon-based material and a coating phase discretely disposed on the surface of the core based on attachment sites. The core includes a silicon-based material, and the coating phase includes at least one of a halide electrolyte and a conductive carbon material. It should be noted that the core can be a single primary particle of silicon-based material, or it can be a secondary particle formed by the aggregation of multiple primary particles of silicon-based material.
[0085] In step S101, at least one of the following methods can be used to form corresponding adhesion sites on the surface of the silicon-based material: hydroxylation modification, amination modification, hydrosilylation modification, wet etching to create pores, and plasma bombardment treatment. In some embodiments, the corresponding adhesion sites are nucleation sites of the coating phase. The adhesion sites include chemically active sites and / or physical anchoring points for forming the coating phase. The chemically active sites include at least one of hydroxyl (-OH), amino (-NH2), and silane (Si-H) groups, and the physical anchoring points include etched structures and / or defect sites.
[0086] In some embodiments, the method of forming attachment sites on the surface of silicon-based materials is hydroxylation modification. Specifically, the silicon-based material is etched in an oxidizing solution such as hydrogen peroxide or concentrated sulfuric acid, or subjected to plasma oxidation treatment, so that the bonds on the surface of the silicon-based material are broken and combined with oxygen to generate hydroxyl groups. In this scenario, the attachment sites are hydroxyl groups.
[0087] In some embodiments, the method of forming adhesion sites on the surface of silicon-based materials is amylation modification. Specifically, the silicon-based materials are surface-treated with an aminosilane coupling agent, the siloxane group at one end of the aminosilane coupling agent molecular chain combines with the hydroxyl group on the surface of the silicon-based materials, and the amino group at the other end of the aminosilane coupling agent molecular chain is exposed to form adhesion sites.
[0088] In some embodiments, the method of forming adhesion sites on the surface of silicon-based materials is hydrosilylation modification. Specifically, by means of hydrofluoric acid etching or gas-phase hydrogen reduction treatment, silane groups are introduced on the surface of silicon-based materials. In this scenario, the adhesion sites are silane groups.
[0089] In some embodiments, the method of forming adhesion sites on the surface of silicon-based materials is wet etching to create holes. Specifically, anisotropic etching is performed on the surface of silicon-based materials using a mixed solution of hydrofluoric acid and nitric acid to form nanoscale pores, trenches, and other etching structures on the surface of silicon-based materials. In this scenario, the adhesion sites are nanoscale etching structures.
[0090] In some embodiments, the method of forming attachment sites on the surface of silicon-based materials is plasma bombardment treatment. Specifically, plasma formed by argon, nitrogen, etc. is used to bombard the silicon-based materials. The plasma will destroy the crystal structure on the surface of the silicon-based materials and form a large number of defect sites such as vacancies and dislocations. In this scenario, the attachment sites are defect sites.
[0091] It is understandable that the attachment sites formed on the surface of the silicon-based material in step S101 are attachment sites discretely set on the surface of the silicon-based material, and the coating phase prepared based on the attachment sites in step S102 is also discretely set on the core surface.
[0092] The attachment sites are highly reactive sites on the surface of silicon-based materials. In step S102, the coating phase will preferentially nucleate and grow in situ at the highly reactive attachment sites on the core surface. By controlling the growth size of the coating phase, a coating phase discretely set on the core surface can be obtained, thereby obtaining the negative electrode active material.
[0093] Specifically, in step S102, when the coating phase includes a halide electrolyte, the halide electrolyte can be prepared in situ at the attachment site using at least one of site-selective liquid phase deposition, vapor phase deposition-etching synergistic method, and in-situ precipitation method. When the coating phase includes a conductive carbon material, the conductive carbon material can be prepared in situ at the attachment site using at least one of site-defined polymer pyrolysis method, site anchoring method for carbon nanoparticles, and plasma-assisted in-situ growth method.
[0094] In some embodiments, the coating phase includes a halide electrolyte and a conductive carbon material. If the halide electrolyte is discretely disposed on a portion of the core surface, and the conductive carbon material is discretely disposed on a portion of the halide electrolyte surface and a portion of the core surface not covered by the halide electrolyte, then the discretely disposed halide electrolyte can first be prepared on the core surface through steps S101 and S102. Then, by a method similar to step S101, attachment sites are formed on the surface of the halide electrolyte. Then, the discretely disposed conductive carbon material is prepared again at the attachment sites on the surface of the halide electrolyte and the surface of the core not covered by the halide electrolyte through step S102.
[0095] In some embodiments, the coating phase includes a halide electrolyte and a conductive carbon material. If the conductive carbon material is discretely disposed on a portion of the core surface, and the halide electrolyte is discretely disposed on a portion of the conductive carbon material surface and a portion of the core surface not covered by the halide electrolyte, then the discretely disposed conductive carbon material can first be prepared on the core surface through steps S101 and S102. Then, by a method similar to step S101, attachment sites are formed on the surface of the conductive carbon material. Then, the discretely disposed halide electrolyte is prepared again at the attachment sites on the surface of the conductive carbon material and the surface of the core not covered by the halide electrolyte through step S102.
[0096] The method for preparing the negative electrode active material provided in this application involves forming corresponding adhesion sites on the surface of a silicon-based material, and then preparing a coating phase based on these adhesion sites to obtain the negative electrode active material. This method allows for the formation of a discretely arranged coating phase on the core surface of the silicon-based material. The high specific capacity of the silicon-based material improves the energy density of the battery. Simultaneously, the discretely arranged halide electrolyte forms multiple ion transport sites on the core surface, compensating for the low intrinsic ionic conductivity of the silicon-based material and improving the ionic conductivity of the negative electrode active material. Furthermore, the discretely arranged conductive carbon material constructs a three-dimensional electron conduction pathway on the core surface, enhancing the electronic conductivity of the negative electrode active material. This improves the charge transport performance of the negative electrode active material from different dimensions, thereby enhancing the rate performance of the battery prepared based on the negative electrode active material provided in this application. In addition, the method of forming corresponding adhesion sites on the surface of the silicon-based material and preparing the coating phase in situ based on these adhesion sites improves the interfacial bonding quality between the coating phase and the core surface, suppresses interfacial side reactions, reduces the continuous increase in interfacial impedance, and helps extend the cycle life of the battery.
[0097] In some embodiments, step S101, which involves forming corresponding adhesion sites on the surface of the silicon-based material, includes: Step S1011: Heat the silicon-based material in a mixed gas environment to obtain a silicon-based material with attachment sites formed on its surface.
[0098] In this embodiment of the application, during the process of forming corresponding attachment sites on the surface of the silicon-based material, the silicon-based material can be heated in a mixed gas environment containing hydrogen through step S1011. This not only forms attachment sites on the surface of the silicon-based material, but also removes the oxide layer on the surface of the silicon-based material, further reducing the charge transport impedance of the negative electrode active material and improving the charge transport performance of the negative electrode active material. In this scenario, the attachment sites include silane groups.
[0099] In step S1011, the mixed gas includes hydrogen and an inert gas, and the proportion of hydrogen in the mixed gas is 1% to 15%. Controlling the proportion of hydrogen in the mixed gas within the range of 1% to 15% can form adhesion sites on the surface of silicon-based materials and remove the oxide layer on the surface of silicon-based materials, while avoiding material structure damage caused by excessive reduction of silicon-based materials, which is beneficial to improving the structural integrity and surface consistency of silicon-based materials.
[0100] The inert gases may include, but are not limited to, Ar, N2, and He. The proportion of hydrogen in the gas mixture can be either by volume or by mass.
[0101] In some embodiments, the temperature for heating the silicon-based material is 300°C to 900°C, and the heating time is 0.5h to 2h, which is beneficial to fully remove the oxide layer on the surface of the silicon-based material and form the required number of adhesion sites on the surface of the silicon-based material.
[0102] In some embodiments, step S102, which involves preparing a coating phase based on the attachment sites to obtain a negative electrode active material, includes: Step S1021: Prepare a liquid dispersion system based on the first target silicon-based material, LiX and MX3.
[0103] Step S1022: Stir the liquid dispersion system to form discretely arranged halide electrolytes on the surface of the first target silicon-based material.
[0104] In this embodiment, the coating phase includes a halide electrolyte. During the preparation of the coating phase based on attachment sites, a liquid dispersion system can be prepared by mixing the first target silicon-based material, LiX, and MX3 in step S1021. Then, the liquid dispersion system is stirred in step S1022, allowing LiX and MX3 to disperse uniformly in the liquid phase. This promotes the synchronous nucleation and growth of the halide electrolyte at different attachment sites on the first target silicon-based material, forming uniformly sized and evenly distributed nanoscale electrolytes. This results in discretely arranged halide electrolytes on the surface of the first target silicon-based material, which improves the consistency of ion transport sites formed by the halide electrolyte on the core surface. This, in turn, improves the uniformity of the ionic conductivity of the negative electrode active material, avoiding problems such as uneven electrode polarization and reduced charge / discharge efficiency caused by local differences in ion transport rates. This further enhances the rate performance and cycle stability of the battery.
[0105] Specifically, in step S1021, firstly, the first target silicon-based material is dispersed in an organic solvent system; then, LiX and MX3 are added to the organic solvent system and mixed evenly to obtain a liquid dispersion system.
[0106] The first target silicon-based material is a silicon-based material with conductive carbon material disposed on its surface or a silicon-based material with adhesion sites formed on its surface. In some embodiments, the first target silicon-based material may be a silicon-based material with adhesion sites formed on its surface obtained by step S101. In this scenario, the surface of the first target silicon-based material does not include a coating phase. In some embodiments, the first target silicon-based material may be a silicon-based material with conductive carbon material disposed on its surface.
[0107] Wherein, X represents a halogen, and exemplarily, X includes any one of Cl, Br, and I; M includes any one of Y, In, Sc, Er, and La. In some embodiments, the molar ratio of Li to M is 3:1.
[0108] The organic solvent includes at least one of anhydrous ethanol and anhydrous isopropanol.
[0109] In step S1022, the liquid dispersion system can be heated to 20℃~60℃ and stirred using microwave-pulse stirring technology to promote the reaction of LiX and MX3 and their nucleation and growth at the attachment sites to obtain halide electrolytes. In this embodiment, by controlling the stirring time, temperature, and amount of LiX and MX3 added to the liquid dispersion system, the size of the halide electrolytes formed at each attachment site can be controlled, preventing the halide electrolytes formed at different attachment sites from connecting to form a continuous coating phase, thus obtaining halide electrolytes discretely disposed on the surface of the first target silicon-based material.
[0110] In some embodiments, after step S1022, the liquid dispersion system can be subjected to solid-liquid separation, and the solid product obtained after solid-liquid separation can be washed and dried to obtain the negative electrode active material provided in the embodiments of this application.
[0111] In some embodiments, the stirring time for the liquid dispersion system is 5 min to 30 min.
[0112] In some embodiments, the pH of the liquid dispersion system is 6.5–8.5, which is beneficial for regulating the reaction kinetics of LiX and MX3, promoting the efficient and mild complexation reaction of LiX and MX3 in the liquid dispersion system to generate halide electrolyte precursors. Simultaneously, it adapts to the chemical activity of the attachment sites, guiding the halide electrolyte precursors to nucleate and grow uniformly at the attachment sites, ultimately forming well-defined and firmly bound halide electrolytes at the attachment sites. Specifically, the pH of the liquid dispersion system can be one of 6.5, 7, 7.5, 8, and 8.5, or any value between two of them.
[0113] In some embodiments, step S102, which involves preparing a coating phase based on the attachment sites to obtain a negative electrode active material, includes: Step S1023: Mix the second target silicon-based material with a carbon source to prepare a mixed raw material.
[0114] Step S1024: Calcine the mixed raw materials to form discretely arranged conductive carbon materials on the surface of the second target silicon-based material.
[0115] In this embodiment, the coating phase includes a conductive carbon material. During the preparation of the coating phase based on attachment sites, a mixed raw material can be prepared by mixing the second target silicon-based material with a carbon source in step S1023. Then, the mixed raw material is calcined in step S1024, causing the carbon source to undergo pyrolysis and carbonization during the calcination process. Based on the anchoring effect of the highly active attachment sites on the surface of the second target silicon-based material, the products after pyrolysis and carbonization of the carbon source are oriented to nucleate and grow synchronously at the attachment sites, forming a uniformly sized and evenly distributed nanoscale conductive carbon material. This improves the distribution consistency, conductivity consistency, and site coverage consistency of the continuous electron transport network formed on the core surface of the conductive carbon material, enhancing the uniformity of the electronic conductivity of the negative electrode active material. It effectively avoids problems such as uneven electrode polarization and reaction rate differences caused by localized electron conduction obstruction, further improving the rate performance of the battery and extending its cycle life.
[0116] In step S1023, the second target silicon-based material and the carbon source can be mixed and ball-milled to obtain a mixed raw material.
[0117] In some embodiments, the mass ratio of the second target silicon-based material to the carbon source is 1:0.25 to 1:0.4. Within this range, the size of the conductive carbon material formed at the attachment site and the loading of the conductive carbon material on the core surface can be controlled. This ensures that the discretely arranged conductive carbon material forms an efficient three-dimensional electronic conduction pathway on the core surface, while avoiding excessive carbon source that could lead to the formation of a continuous coating phase on the core surface. This provides a buffer space for volume changes in the core during charge-discharge cycles, achieving dual optimization of the electronic conduction performance and structural stability of the negative electrode active material. Specifically, the mass ratio of the second target silicon-based material to the carbon source can be one of 1:0.28, 1:0.3, 1:0.32, 1:0.37, and 1:0.4, or any value between two of them.
[0118] In some embodiments, the carbon source includes dopamine hydrochloride.
[0119] In some embodiments, the second target silicon-based material is mixed and ball-milled with a carbon source for 10 to 30 minutes to improve the uniformity of the distribution of each component in the mixed raw material.
[0120] The second target silicon-based material is a silicon-based material with a halide electrolyte on its surface or a silicon-based material with adhesion sites formed on its surface; in some embodiments, the second target silicon-based material is a silicon-based material with a halide electrolyte on its surface; in some embodiments, the second target silicon-based material is a silicon-based material with adhesion sites formed on its surface obtained by step S101, in which case the surface of the second target silicon-based material does not include a coating phase.
[0121] In step S1024, the mixed raw materials can be calcined in a mixed gas environment to promote the pyrolysis and carbonization of the carbon source under calcination conditions. Relying on the anchoring effect of the highly active attachment sites on the surface of the second target silicon-based material, directional nucleation and synchronous growth are achieved to form a uniformly sized and evenly distributed nanoscale conductive carbon material.
[0122] In this embodiment, by controlling at least one of the following: the mass ratio of the second target silicon-based material to the carbon source, the temperature and duration of calcination of the mixed raw materials, and the heating rate, the size of the conductive carbon material formed at each attachment site can be controlled, thus avoiding the conductive carbon materials formed at different attachment sites from connecting to each other to form a continuous coating phase, thereby obtaining conductive carbon materials discretely disposed on the surface of the second target silicon-based material.
[0123] In some embodiments, the gaseous environment for calcining the mixed raw materials includes hydrogen and an inert gas, and the proportion of hydrogen in the mixed gas is 1% to 15%. Hydrogen in the range of 1% to 15% can provide a mild reducing atmosphere for carbon source pyrolysis, accelerate the breaking and recombination of carbon source molecular chains, promote the conversion of amorphous carbon to graphitized carbon, and improve the intrinsic electronic conductivity of conductive carbon materials. At the same time, hydrogen can remove volatile products such as tar and impurities generated during carbon source pyrolysis, preventing them from remaining in the conductive carbon layer and forming insulation defects, which is beneficial to improving the conductivity efficiency of the electron transport network formed by the conductive carbon material.
[0124] In some embodiments, the temperature for calcining the mixed raw materials is 400℃~1000℃. Within this range, not only can the carbon source be fully pyrolyzed and carbonized and moderately graphitized, thus improving the electronic conductivity of the conductive carbon material, but the excessive agglomeration of carbon particles and sintering of silicon-based materials caused by the high temperature of calcination can also be avoided. This allows the conductive carbon material to be uniformly anchored on the attachment sites in a nanoscale discrete form, which is beneficial to improving the electronic conduction efficiency and cycle structure stability of the negative electrode active material.
[0125] In some embodiments, the heating rate of the mixed raw materials for calcination is greater than or equal to 30°C and the calcination time of the mixed raw materials is less than or equal to 15 minutes. This can achieve rapid pyrolysis of the carbon source, increase the nucleation rate of the products after carbonization of the carbon source at the attachment site, inhibit the excessive agglomeration of carbon particles to form continuous conductive carbon materials, and facilitate the formation of discretely distributed, uniformly sized conductive carbon materials on the core surface.
[0126] In some embodiments, the calcination time of the mixed raw materials is 5 min to 15 min. Within this range, it can not only promote the full pyrolysis and carbonization of the carbon source to effectively nucleate at the attachment site and improve the interfacial bonding quality between the conductive carbon material and the core, but also limit the excessive growth of the conductive carbon material and avoid the formation of a continuous conductive carbon material coating phase on the core surface. At the same time, the short-time calcination process can adapt to the requirements of rapid heating, improve the production efficiency of the negative electrode active material, reduce the production energy consumption of the negative electrode active material, and thus improve the electrochemical performance and industrialization feasibility of the negative electrode active material.
[0127] This application also provides a negative electrode sheet, which includes the negative electrode active material as described above, or the negative electrode sheet includes a negative electrode active material prepared by the method for preparing the negative electrode active material as described above.
[0128] Specifically, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative active material layer includes the negative active material as described in the above embodiments, or includes the negative active material prepared by the negative active material preparation method embodiments described above.
[0129] In some embodiments, the negative current collector may include, but is not limited to, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, composite current collector, etc.
[0130] The negative electrode active material layer also includes conductive agents and binders. The conductive agents may include, but are not limited to, Super P Conductive Carbon Black (SP), Ketjen Black (KB), Acetylene Black (AB), Carbon Nanotubes (CNT), Carbon Nanofibers (CNF), Graphene (GN), Reduced Graphene Oxide (rGO), and Graphene Nanosheets (GNS). The binders may include, but are not limited to, Poly(vinylidene fluoride) (PVDF), Carboxymethyl Cellulose Sodium (CMC), and Styrene-Butadiene Rubber (SBR).
[0131] The above-described negative electrode plate embodiment includes the aforementioned negative electrode active material and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description in the negative electrode active material embodiment section.
[0132] This application also provides a battery, which includes the negative electrode sheet as described above.
[0133] In some embodiments, the battery may include, but is not limited to, all-solid-state batteries, semi-solid-state batteries, and liquid batteries.
[0134] The battery also includes a positive electrode and an electrolyte disposed between the positive and negative electrodes. Specifically, the positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector, the positive active material layer including a positive active material.
[0135] In some embodiments, the positive electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the positive electrode current collector is a carbon material, and the form of the positive electrode current collector may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc.
[0136] In some embodiments, the positive electrode active material may include, but is not limited to, lithium cobalt oxide (LiCoO2) and ternary nickel cobalt manganese oxide (LiNiO2). x Co y Mn _z O2, NCM), ternary nickel-cobalt-aluminum oxide (LiNi) x Coy Al _z Lithium manganese oxide (LiMnO2), lithium spinel manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), and lithium-rich manganese-based materials, etc.
[0137] The positive electrode active material layer also includes conductive agents and binders. The conductive agents may include, but are not limited to, conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, reduced graphene oxide, and graphene nanosheets. The binders may include, but are not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
[0138] The electrolyte acts as a conductor of ions between the positive and negative electrodes. The electrolyte can be liquid, gel-like, or entirely solid. In some embodiments, the electrolyte is a liquid electrolyte solution comprising an electrolyte salt and a solvent. The electrolyte salt is a lithium salt, and the solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the organic solvent includes ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.
[0139] In some embodiments, the electrolyte is a solid electrolyte, which may be a sulfide solid electrolyte; the sulfide solid electrolyte includes at least one of the following: Li10GeP2S12 type, Thio-LISICON type, Li2S-P2S5 type, and silver-germanium sulfide type.
[0140] The battery embodiments described above include the aforementioned negative electrode active material and achieve the same technical effect. To avoid repetition, they will not be repeated here. For relevant details, please refer to the description in the negative electrode active material embodiment section.
[0141] This application also provides a vehicle that includes the battery described above, the battery serving as a power source for the vehicle.
[0142] In some embodiments, the vehicle may be a motor vehicle, such as a passenger car, a truck or its derivatives; it may also be a special vehicle, such as a tractor, an excavator, a fire truck, an ambulance, etc.; it may also be a water vehicle, such as an amphibious vehicle; or it may be a rail transit vehicle, such as a train, a subway, a tram, etc.
[0143] The above-described vehicle embodiments include the aforementioned negative electrode active material and achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description in the negative electrode active material embodiment section.
[0144] This application embodiment also provides an electrical device, which includes the battery as described above, and the battery serves as the power supply for the electrical device.
[0145] The battery can be a power source for the electrical device or an energy storage unit for the electrical device. Electrical devices can include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be, for example, mobile phones, laptops, etc.; electric vehicles can be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0146] The above-described electrical device embodiment includes the aforementioned negative electrode active material and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description in the negative electrode active material embodiment section.
[0147] The present application will be described in detail below through embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0148] Example 1 (1) Preparation of silicon-based materials: 20g of SiO powder with a particle size of 150nm was loaded into a quartz boat, placed in a tube furnace, and H2 / Ar (volume ratio 5:95) was introduced. The furnace was kept at 600℃ for 1h to form Si-H adhesion sites on the surface of the silicon-based material, thus obtaining powder A.
[0149] (2) Preparation of negative electrode activity: First, dissolve 3 mmol LiCl and 1 mmol InCl3 in 200 mL of anhydrous isopropanol, sonicate for 10 min, and then add powder A prepared in step (1) to obtain a liquid dispersion system. Then, microwave-pulse stir the liquid dispersion system at 40 °C for 20 min, and add 0.5 mL of 1 mol L to the liquid dispersion system dropwise. -1The LiBH4-ether solution was maintained at pH≈8 and stirred for 5 min to form discrete halide electrolytes on the surface of powder A. After removing anhydrous isopropanol by rotary evaporation, the powder was vacuum dried at 60 °C for 4 h to obtain Si@Li3InCl6, denoted as powder B. Then, 5 g of powder B was dispersed in 50 mM Tris-HCl buffer (pH 8.5), and 1.5 g of dopamine hydrochloride was added. After magnetic stirring at room temperature for 4 h, the powder was centrifuged and washed. The resulting solid product was placed in a quartz tube, Ar / 5% H2 was introduced, and the temperature was increased to 700 °C at 40 °C / min and held for 10 min. After cooling, the discrete halide-conductive carbon material dual-spot coated negative electrode active material was obtained, denoted as S-Hal-C.
[0150] (3) Battery fabrication: The S-Hal-C prepared in step (1) and Li3InCl3 were pressed into a tablet at a mass ratio of 8:2 to prepare a working electrode. The working electrode and the lithium sheet counter electrode were then assembled to obtain an all-solid-state button half-cell.
[0151] Examples 2-34 The difference between Examples 2-34 and Comparative Example 1 is that: By adjusting the process parameters in step (1) and / or step (2), the product parameters of the core and the coating phase in the negative electrode active material are adjusted. The relevant parameters of the negative electrode active materials prepared by Examples 1 to 34 are shown in Table 1.
[0152] Table 1
[0153] In Table 1, the lateral dimension refers to the dimension of the coating phase in the direction parallel to the core surface. D / I G This represents the ratio of the intensity of the D peak to the intensity of the G peak in the Raman spectrum of a conductive carbon material.
[0154] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: Step (1) is excluded; In step (2), SiO powder with a particle size of 150 nm is used as the negative electrode active material.
[0155] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In step (2), the duration of microwave-pulse stirring is extended to 120 min, and the pH is not adjusted by adding LiBH4-ether solution. A continuous halide electrolyte coating phase is formed on the core surface to obtain the negative electrode active material, denoted as Con-Hal.
[0156] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is as follows: In step (2), 5g of SiO powder with a particle size of 150nm was dispersed in 50 mM Tris-HCl buffer (pH 8.5), and 1.5g of dopamine hydrochloride was added. After stirring magnetically for 4h at room temperature, the mixture was centrifuged and washed. The resulting solid product was placed in a quartz tube, Ar / 5% H2 was introduced, and the temperature was increased to 700℃ at 10℃ / min and held for 60min. After cooling, the conductive carbon material was continuously coated with the negative electrode active material, which was denoted as Con-C.
[0157] Test method: (1) Ionic conductivity test: At 25°C, a 10mV AC disturbance voltage was applied to the test battery, and at 10... -2 Hz~10 6 EIS spectra were acquired by scanning within the Hz frequency range, and the total ion transport resistance Rion of the high-frequency region and the real axis intercept in the spectrum was read. The actual thickness L of the test cell was measured, and the effective conductive area S was determined using the formula: σ i The ionic conductivity of the negative electrode active material is calculated as L / (Rion×S).
[0158] (2) Electronic conductivity test: At 25℃, the test battery is clamped in a four-probe tester, and a constant DC current of 100μA~1mA is applied. The voltage drop V between the inner probes is measured. The actual thickness d of the test battery is measured, and the effective conductive area S is determined using the formula: σ e The electronic conductivity of the negative electrode active material is calculated as I×ln2 / (π×d×V).
[0159] (3) Cyclic performance test: At 25℃, the test battery was charged and discharged at a rate of 0.5C within the range of 3V to 4.3V, and the initial discharge capacity C1 was measured. After 500 cycles at the same rate and voltage range, the discharge capacity C2 of the 500th cycle was measured. The capacity retention rate after 500 cycles was calculated using the formula: Capacity retention rate = C2 / C1 × 100%.
[0160] (4) Test of the breakage rate of the negative electrode active material: Under 25℃ conditions, the test battery after 500 cycles was disassembled, and a cross-sectional sample of the negative electrode active material layer was taken and characterized by SEM. The total number of negative electrode active material particles N0 in the field of view was selected and the number of broken particles N1 was counted. The breakage rate of the negative electrode active material was calculated by the formula: breakage rate = N1 / N0×100%.
[0161] The batteries prepared by Examples 1-34 and Comparative Examples 1-3 were subjected to the above-mentioned ionic conductivity test, electronic conductivity test, cycle performance test and negative electrode active material damage rate test. The test results are shown in Table 2.
[0162] Table 2
[0163] Based on the test data in Table 2, the ionic conductivity of the batteries prepared by Examples 1-34 remained at 6.2 × 10⁻⁶. -6 The electronic conductivity remains above 0.1 S / cm, and compared with Comparative Examples 1-3, the capacity retention rate of the batteries prepared by Examples 1-34 is improved by more than 16%, and the breakage rate of the negative electrode active material is reduced by more than 69.7%. It can be seen that the embodiments of this application can improve the ionic conductivity and electronic conductivity of the negative electrode active material, while also improving the cycle capacity retention rate based on the negative electrode active material and reducing the probability of particle breakage and pulverization of the negative electrode active material during charge and discharge cycles. This is not only beneficial to improving the rate performance of the battery, but also to extending the cycle life of the battery.
[0164] In summary, the negative electrode active material provided in this application includes a core and a coating phase discretely disposed on the surface of the core. The core comprises a silicon-based material, and the coating phase comprises at least one of a halide electrolyte and a conductive carbon material. The silicon-based material has a high theoretical specific capacity, which is beneficial for improving the energy density of the battery. The halide electrolyte has excellent ion conductivity, which can compensate for the low intrinsic ion conductivity of the silicon-based material, providing an efficient transport channel for the rapid insertion and extraction of active ions and reducing the ion transport resistance of the negative electrode active material. The conductive carbon material has excellent electronic conductivity, enabling the construction of continuous electron transport on the surface of the core. The coating network improves the electronic conductivity of silicon-based materials and reduces the electron transport resistance of the negative electrode active material. Furthermore, when the coating phase includes a halide electrolyte, the discretely arranged halide electrolyte can form multiple ion transport sites on the core surface, thereby increasing the migration rate of active ions. When the coating phase includes a conductive carbon material, the discretely arranged conductive carbon material can construct a three-dimensional electron conduction pathway on the core surface, reducing the electron transport impedance of the negative electrode active material. This can improve the charge transport performance of the negative electrode active material from different dimensions, thereby improving the rate performance of the battery prepared based on the negative electrode active material provided in the embodiments of this application.
[0165] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0166] The foregoing has provided a detailed description of the negative electrode active material, preparation method, electrode sheet, battery, vehicle, and electrical device provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A negative electrode active material, characterized in that, It includes a core and a coating phase discretely disposed on the surface of the core, wherein the core comprises a silicon-based material and the coating phase comprises at least one of a halide electrolyte and a conductive carbon material.
2. The negative electrode active material according to claim 1, characterized in that, The thickness of the coating phase is 1 nm to 30 nm and / or, The coating phase has a size of 10 nm to 100 nm in the direction parallel to the core surface; and / or, The coating phase has a coverage rate of 20% to 95% on the core surface.
3. The negative electrode active material according to claim 1 or 2, characterized in that, The coating phase comprises a halide electrolyte, wherein the halide electrolyte satisfies at least one of the following: (1) The thickness of the halide electrolyte is 2nm~30nm; (2) The size of the halide electrolyte in the direction parallel to the core surface is 10 nm to 80 nm; (3) The coverage of the halide electrolyte on the core surface is 30%~80%; (4) The halide electrolyte includes at least one of Li3MX6 and LiMX4, wherein X includes any one of Cl, Br and I, and M includes any one of Y, In, Sc, Er and La.
4. The negative electrode active material according to claim 3, characterized in that, The thickness of the halide electrolyte is 5 nm to 15 nm; and / or, the size of the halide electrolyte in the direction parallel to the core surface is 20 nm to 60 nm.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that, The coating phase comprises a conductive carbon material, and the conductive carbon material satisfies at least one of the following: (1) The thickness of the conductive carbon material is 1 nm to 10 nm; (2) The conductive carbon material has a size of 10 nm to 100 nm in the direction parallel to the core surface; (3) The conductive carbon material has a coverage rate of 20% to 70% on the surface of the core; (4) In the Raman spectrum of the conductive carbon material, the ratio of the intensity of the D peak to the intensity of the G peak is less than or equal to 1.1; (5) The in-plane reversible elongation of the conductive carbon material is greater than or equal to 10%; (6) The conductive carbon material includes atomically doped graphitized carbon.
6. The negative electrode active material according to claim 5, characterized in that, The thickness of the conductive carbon material is 2nm to 8nm.
7. The negative electrode active material according to any one of claims 1 to 6, characterized in that, The silicon-based material includes at least one of elemental silicon and silicon oxide.
8. The negative electrode active material according to any one of claims 1 to 7, characterized in that, The coating phase includes a halide electrolyte and a conductive carbon material; wherein the halide electrolyte is discretely disposed on a portion of the surface of the core, and the conductive carbon material is discretely disposed on a portion of the surface of the halide electrolyte and / or the portion of the surface of the core not covered by the halide electrolyte.
9. The negative electrode active material according to claim 8, characterized in that, The overlap area between the halide electrolyte and the conductive carbon material accounts for 10% to 40% of the core surface area; and / or, The halide electrolyte and the conductive carbon material have an overlapping region, in which the halide electrolyte and the conductive carbon material are chemically bonded.
10. The negative electrode active material according to any one of claims 1 to 9, characterized in that, The proportion of the exposed area on the surface of the core that is not covered by the coating phase is 5% to 80%.
11. The negative electrode active material according to claim 10, characterized in that, The proportion of the exposed area on the surface of the core that is not covered by the coating phase is 5% to 40%.
12. The negative electrode active material according to any one of claims 1 to 11, characterized in that, The primary particle size in the core is 50nm~500nm; and / or, The core includes channels with a diameter of 2nm to 50nm.
13. The negative electrode active material according to any one of claims 1 to 12, characterized in that, The negative electrode active material has an ionic conductivity greater than or equal to 1×10⁻⁶ at 25°C. -4 S / cm; and / or, The negative electrode active material has an electronic conductivity greater than or equal to 1 S / cm at 25°C.
14. A method for preparing a negative electrode active material, characterized in that, The method for preparing the negative electrode active material according to any one of claims 1 to 13 includes: Forming corresponding adhesion sites on the surface of silicon-based materials; Based on the attachment sites, a coating phase is prepared to obtain a negative electrode active material.
15. The preparation method according to claim 14, characterized in that, The process of forming corresponding adhesion sites on the surface of the silicon-based material includes: Silicon-based materials are heated in a mixed gas environment to obtain silicon-based materials with adhesion sites on their surface; The mixed gas includes hydrogen and an inert gas, and the proportion of hydrogen in the mixed gas is 1% to 15%.
16. The preparation method according to claim 14 or 15, characterized in that, The preparation of the coating phase based on the attachment sites to obtain the negative electrode active material includes: A liquid dispersion system is prepared based on the first target silicon-based material, LiX and MX3, wherein X includes any one of Cl, Br and I, and M includes any one of Y, In, Sc, Er and La. The first target silicon-based material is a silicon-based material with conductive carbon material disposed on its surface or a silicon-based material with attachment sites formed on its surface. The liquid dispersion system is stirred to form discretely arranged halide electrolytes on the surface of the first target silicon-based material; The pH value of the liquid dispersion system is 6.5 to 8.
5.
17. The preparation method according to claim 14 or 15, characterized in that, The preparation of the coating phase based on the attachment sites to obtain the negative electrode active material includes: The second target silicon-based material is mixed with a carbon source to prepare a mixed raw material. The second target silicon-based material is a silicon-based material with a halide electrolyte on its surface or a silicon-based material with adhesion sites formed on its surface. The mixed raw materials are calcined to form discretely arranged conductive carbon materials on the surface of the second target silicon-based material; The preparation method satisfies at least one of the following: (1) The mass ratio of the second target silicon-based material to the carbon source is 1:0.25 to 1:0.4; (2) The gaseous environment in which the mixed raw materials are calcined includes hydrogen and inert gas, and the proportion of hydrogen in the mixed gas formed by hydrogen and inert gas is 1% to 15%; (3) The temperature for calcining the mixed raw materials is 400℃~1000℃; (4) The heating rate of the mixed raw material for calcination is greater than or equal to 30°C, and the calcination time of the mixed raw material is less than or equal to 15 min; (5) The calcination time for the mixed raw materials is 5 min to 15 min.
18. A negative electrode sheet, characterized in that, It includes the negative electrode active material as described in any one of claims 1 to 13, or the negative electrode active material prepared by the preparation method of the negative electrode active material as described in any one of claims 14 to 17.
19. A battery, characterized in that, Includes the negative electrode sheet as described in claim 18.
20. A vehicle, characterized in that, Includes the battery as described in claim 19, wherein the battery serves as a power source for the vehicle.
21. An electrical appliance, characterized in that, Includes the battery as described in claim 19, wherein the battery serves as the power supply for the electrical device.